CPA Examination: Accounting Practice, Part II. - Chamberlain, John H. (The Accounting Review, 1966)
Abstract The article presents various problems prepared by the Board of Examiners of the U.S. body American Institute of Certified Public Accountants and presented at the second half of the certified public accountant examination in accounting practice on November 4, 1965. The candidates were required to solve all problems. The suggested time allowances for various problems were also given. One of the problems talked about the budget expenditures of the Board of Education of the Victoria School District for the year ending June 30, 1967. Data given included that the estimated average daily school enrollment of the School District is 3,000 pupils including 200 pupils enrolled in a vocational training program, estimated revenues include equalizing grants-in-aid from the state of $150 per pupil and that the grants were established by state law under a plan intended to encourage raising the level of education. The students were asked to prepare a schedule computing the estimated total funds to be obtained from local taxation for the ensuing school year ending June 30, 1967 for the Victoria School District.